Cre-inducible Adeno Associated Virus-mediated Expression of P301L Mutant Tau Causes Motor Deficits and Neuronal Degeneration in the Substantia Nigra. (1st December 2019) - You, Yang; Botros, Mina B.; Enoo, Alicia A. Van; Bockmiller, Aaron; Herron, Shawn; Delpech, Jean Christophe; Ikezu, Tsuneya
Highlights: Cre-inducible P301L tau expression in the dopaminergic neurons of substantia nigra. Induction of motor deficits over a short time course. Loss of dopaminergic neurons and accumulation of phosphorylated tau. Abstract: Accumulation of microtubule associated protein tau in the substantia nigra is associated with several tauopathies including progressive supranuclear palsy (PSP). A number of studies have used mutant tau transgenic mouse model to mimic the neuropathology of tauopathies and disease phenotypes. However, tau expression in these transgenic mouse models is not specific to brain subregions, and may not recapitulate subcortical disease phenotypes of PSP. It is necessary to develop a new disease modeling system for cell and region-specific expression of pathogenic tau for modeling PSP in mouse brain. In this study, we developed a novel strategy to express P301L mutant tau to the dopaminergic neurons of substantia nigra by coupling tyrosine hydroxylase promoter Cre-driver mice with a Cre-inducible adeno-associated virus (iAAV). The results showed that P301L mutant tau was successfully transduced in the dopaminergic neurons of the substantia nigra at the presence of Cre recombinase and iAAV. Furthermore, the iAAV-tau-injected mice displayed severe motor deficits including impaired movement ability, motor balance, and motor coordination compared to the control groups over a short time-course. Immunochemical analysis revealed that tau gene transfer significantly resulted in loss of tyrosine hydroxylase-positive dopaminergic neurons and elevated phosphorylated tau in the substantia nigra. Our development of dopaminergic neuron-specific neurodegenerative mouse model with tauopathy will be helpful for studying the underlying mechanism of pathological protein propagation as well as development of new therapies.